Hollow polypyrrole @ MnO2 spheres as nano-sulfur hosts for improved lithium-sulfur batteries. (10th January 2018) - Li, Yong; Shi, Bin; Liu, Wen; Guo, Rui; Pei, Haijuan; Ye, Daixin; Xie, Jingying; Kong, Jilie
Abstract: The lithium-sulfur battery is an ideal energy storage system owing to its high energy density. However, the implementations are still thwarted by dramatic capacity decay caused by the dissolution of lithium polysulfides, the low conductivity and the structural instability of the sulfur cathode originated from the volumetric changes during the charging/discharging process. Here, we design and synthesize polypyrrole (PPy)@MnO2 @S spheres with dual core-shell structure. The sulfur nanoparticles (∼80 nm) located into the inside of the composite spheres facilitate fast Li + storage. The polar MnO2 hollow spheres can not only provide enough inner space for alleviating the volume expansion for sulfur, but also effectively moderate the dissolution of polysulfides by synergistic effect of structural restriction and chemical adsorption. Additionally, the second shell consists of PPy nano-particles serve as conductive frameworks and generate sufficient electrical conduction paths. The initial capacities of PPy@MnO2 @S composite are up to 1488.1, 1132.6, 925.7 and 736.7 mAh g −1 at 0.1 C, 0.2 C, 0.5 C and 1 C, respectively. And a small capacity decay rate of 0.048% per cycle is achieved at the rate of 0.5 C over 500 cycles with an areal density of 3.3 mg cm −2 . The strategy may represent an efficient way to realize excellent performance for Li sulfur batteries.